PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP KINERJA INTELLECTUAL CAPITAL (Studi kasus pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2018-2020) - Rizki Fitrian Putra; Nur Diana; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to determine the effect of managerial ownership, institutional ownership, foreign ownership, government ownership, firm size and firm age on intellectual capital performance. A case study on a banking company listed on the IDX. The observation period in this study is 2018-2020. The sample used in this study came from all subgroups in the banking industry sector using purposive sampling method. The research method used to analyze with multiple linear regression test with t-test as a hypothesis tester. Simultaneous test results show that Managerial Ownership, Institutional Ownership, Foreign Ownership, Government Ownership, Company Size and Company Age have an effect on Intellectual Capital.Keywords : Managerial Ownership, Institutional Ownership, Foreign Ownership, Government Ownership, Company Size, Company Age, Intellectual Capital